THE COMPETITIVE ADVANTAGES OF IMPLEMENTING AN ESG (ENVIRONMENTAL, SOCIAL AND GOVERNANCE) AGENDA IN AGRIBUSINESS - Aparecida Nogueira Cardoso, Pâmela; Edemar Ferrarezi Junior; Deléo Rodrigues, Alice (Revista Interface Tecnológica, 2025)
This article aims to discuss the competitive advantages of implementing an ESG Agenda in agribusiness companies and its economic importance. To this end, a qualitative and descriptive bibliographic research was chosen as the methodology to obtain information on the subjects involving the chosen theme. The results show that agribusiness is an essential sector for the local and global economy. Therefore, for companies in this sector to be recognized, their activities must be based on the ESG premises: environmental, social and governance. Thus, it is concluded that through this agenda, agribusiness companies achieve two main competitive advantages: recognition in the market and consequently revenues, according to JBS S/A, which between 2020-2023, even in the face of market challenges, managed to maintain balanced consolidated revenues with a higher percentage of 6% between 2020-2021; 1% higher in the period between 2021-2022 and 1% lower between 2022-2023.
Keywords: ESG Agenda; Competitive Advantages; Social Responsibility; Agribusiness